Nucleotide sequence of the plasminogen activator gene of Yersinia pestis: relationship to ompT of Escherichia coli and gene E of Salmonella typhimurium. - Sodeinde, O A (1989)
We have determined the nucleotide sequence of the 1.4-kilobase DNA fragment containing the plasminogen activator gene (pla) of Yersinia pestis, which determines both plasminogen activator and coagulase activities of the species. The sequence revealed the presence of a 936-base-pair open reading frame that constitutes the pla gene. This reading frame encodes a 312-amino-acid protein of 34.6 kilodaltons and containing a putative 20-amino-acid signal sequence. The presence of a single large open reading frame is consistent with our previous conclusion that the two Pla proteins which appear in the outer membrane of pla+ Y. pestis are derived from a common precursor. The deduced amino acid sequence of Pla revealed that it possesses a high degree of homology to the products of gene E of Salmonella typhimurium and ompT of Escherichia coli but does not possess significant homology to other plasminogen activators of known sequence. We also identified a transcription unit that resides on the complimentary strand and overlaps the pla gene.